Healthcare-Associated-Infections: preliminary results from a realtime reporting system of an Italian neurologic research hospital - Blandi, Lorenzo; Bolcato, Vittorio; Meloni, Alessandro; Bosone, Daniele; Odone, Anna (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Healthcare-Associated-Infections are a critical concern in healthcare settings, posing serious threats to patient safety and causing significant morbidity, mortality, and financial strain. This study aims to calculate healthcare-associated-infections trends in the hospital setting through an automatic reporting system.Study design. The study is a descriptive analysis of automatically generated trends of an innovative digital tool based on existing hospital information flows.Methods. An algorithm was developed within a Clinical Information System to create a suite of quality indicators for monitoring healthcare-associated-infections trends. The algorithm used criteria related to admission, laboratory tests and antimicrobial administrations. A descriptive analysis was conducted for patients aged 18 or older, admitted to a neurological or to a neurorehabilitation department of a neurologic hospital from 2019 to 2022. Results. The results showed fluctuations in healthcare-associated-infections prevalence from 2.9% to 5.6% and hospital infections prevalence from 4.5% to 10.9%, with notable increases in 2020 and 2021. The majority (70.3%) of healthcare associated infections identified by the tool were confirmed to be potentially hospital-acquired, according to the European Centre of Disease Prevention and Control’s definition.Discussion and Conclusions. The study posits the algorithm as a vital tool for automatically monitoring hospital infections, providing valuable preliminary results for improving care quality and guiding the infections’ prevention and control strategies, with plans to benchmark the algorithm against a gold standard in the future.